Relationship between the six-minute walk test and the two-chair test in young adults: a brief review - Bhana, Amandeep; Sikka, Gitanjali (International Journal of Research in Medical Sciences, 2024)
As a useful submaximal exercise test for determining functional capacity in cardio-respiratory disorders, the six-minute walk test (6MWT) has gained recognition. But its practical limitations—such as the requirement for a 30-meter corridor and time constraints—present difficulties, particularly for people with restricted mobility. As a quick and effective substitute, the Two Chair Test (2CT) is suggested and assessed in this study. The integrated physiological responses from several exercise-related systems are captured by the sub-maximal character of the 2CT and 6MWT. The 2CT examines post-exercise changes in PR and SpO2 for two minutes in a unique way, while the 6MWT primarily measures distance. The effectiveness and dependability of the 2CT will be verified using standard physiological assessment metrics from cardiopulmonary exercise testing. To summarise, the objective of this research is to thoroughly verify the Two Chair Test, investigate any potential associations with the Six-Minute Walk Test, and evaluate the effects of the test on arterial oxygen saturation and heart rate. The possible consequences encompass providing a more easily available, effective, and targeted substitute for evaluating functional capacity in various healthcare environments.